Implementasi Kebijakan Hukum Terpadu Dalam Upaya Penurunan Stunting di Kabupaten Gunung Mas - Edelweisia Cristiana; Riwun; Sri Kayun; Herwandi (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Stunting remains a critical public health issue in Gunung Mas, Central Kalimantan. This article aims to analyze the implementation of integrated legal policies in addressing stunting in Kurun Subdistrict using a juridical-empirical approach. The study highlights that despite various intervention programs such as community health posts (Posyandu), nutrition counseling, and the involvement of women’s groups (PKK), there is no local regulation that specifically governs stunting reduction. Research findings indicate that weak intersectoral coordination, limited access to health services, and low nutrition literacy are major obstacles. Conversely, the engagement of traditional leaders and local innovations like Jaga Huma Lewu hold great potential if formally integrated into policy. This study contributes to strengthening the legal perspective within child health policies and emphasizes the urgency of participatory and socially just local legislation. Thus, an adaptive and responsive legal approach is crucial for realizing children's rights protection and ensuring the sustainability of stunting reduction programs in underdeveloped regions.